Stamec-Gravitism: A Simple Theoretical Study to Inspire a Prototype Fabrication for Mobile Perpetual Electricity Generator - Yosua Pratama Iswahyudi; Hendry Izaac Elim (SCIENCE NATURE, 2020)
This novel research presents a theoretical work and its simple simulation as a breakthrough way to derive a mobile electricity apparatus with the weight of ~5 kg generated by an eternal gravity force on earth. The theoretical research was extracted in such a guide simply by incorporating statistical mechanics, classical mechanics and basic theory of electricity and magnetism. In the above-mentioned smart calculation, ones obtain the definition of a constant temperature particularly in isothermal enviromental nature. Furthermore, by solving the whole basic physics relationship with gravity source of power, the electrical energy formula was excerpted with the simplification through a Stamec-Gravitism: a simple theoretical study to inspire a prototype fabrication for mobile perpetual electricity generator. Furthermore, the work is sustained with its simulation results to find out the working physical parameters for normal use of alternating current (AC) electricity system with frequency of 50 Hz and electrical power of ~100 Watt for each proposed apparatus. This research suggests a bright future for the light mobile electricity generator for the needy and the poor in every different nations and tribes consisted of thousands of small islands because it does not need battery storage to work in any different conditions and weather so that such novel work can contribute in a large scale to mitigate natural disasters on earth by implementing it in all human being daily activities based energy uses.